I Love You Tomorrow: Prokrastinasi Akademik dan Manajemen Waktu - Kartadinata, Iven; Tjundjing, Sia (Faculty of Psychology, Universitas Surabaya, 2008)
The aim of this study is to explore the correlation between time management and academic procrastination. Participants (N = 227) were psychology students from the 2004 and 2005 generations. Data were collected through the Time Management Behavior Scale (TMBS) and adapted Procrastination Assessment Scale for Student (PASS). The linear regression analysis and Pearson product moment correlation were used to assess the results. Results indicated a significant negative (– 0.377) correlation between time management and procrastination. The second part of PASS reveals the dominant reasons for procrastination among others: laziness, feeling overwhelmed, unable to manage time properly, and difficulty to make decisions. Whether procrastination is a trait or state behavior is dicussed as well. Penelitian ini bertujuan mendalami hubungan antara manajemen waktu dan prokrastinasi akademik. Partisipan adalah mahasiswa psikologi (N = 227) angkatan 2004 dan 2005. Data diperoleh melalui pengisian Time Management Behavior Scale (TMBS) dan Procrastination Assessment Scale for Student (PASS). Data dianalisis dengan analisis regresi linear dan korelasi product moment dari Pearson. Hasil menunjukkan korelasi negatif (– 0.377) antara pengelolaan waktu dan prokrastinasi akademik. Bagian kedua PASS mengungkap alasan paling dominan prokrastinasi: rasa malas, rasa kewalahan, tak mampu mengatur waktu dengan baik, dan sulit membuat putusan. Didiskusikan apakah prokrastinasi merupakan perilaku bawaan (trait) atau situasional (state).